Integrating research and system-wide practice in public health to enhance the evidence-base of interventions: lessons learnt from Better Start Bradford. (November 2018) - Dickerson, Josie; Bird, Philippa K; Bryant, Maria; Dharni, Nimarta; Bridges, Sally; Willan, Kathryn; Ahern, Sara; Dunn, Abigail; Nielsen, Dea; Uphoff, Eleonora P; Bywater, Tracey; Bowyer-Crane, Claudine; et al.
Abstract: Background: Many interventions that are delivered within public health services have little evidence of effectiveness. An efficient way to improve the evidence-base of public health interventions is to integrate research into system-wide practice, and to evaluate interventions in partnership with stakeholders and the local community. Evaluation of interventions that are being delivered as a part of usual practice offers valuable opportunities to contribute to the evidence base but also generates challenges. We aimed to develop innovative methods and pragmatic strategies to overcome these challenges and achieve relevant and robust evaluations within a complex and changing system. Methods: Better Start Bradford is a partnership programme offering multiple public health interventions to young families in Bradford, a deprived and ethnically diverse northern city in the UK. Between Jan 1, 2016, and Dec 31, 2017, we have worked to integrate research and practice across these multiple interventions. We identified challenges and used a codesign approach to develop strategies to overcome them across five core stages: engaging the community and stakeholders; clarifying the design of the intervention; harnessing routinely collected data; monitoring implementation; and evaluating the process and outcomes using innovative methods. Findings: As a result of our learning we developed comprehensive toolkits: an operational guide through the service design process including templates to ensure that evaluation needs are considered alongside operational plans; an implementation and monitoring guide including methods for selecting progression criteria to monitor performance; and an evaluation framework that incorporates implementation evaluations to enable understanding of intervention performance in practice, and quasi-experimental approaches to infer causal effects in a timely manner. We also offer strategies to harness routinely collected data to enhance the efficiency and affordability of evaluations that are directly relevant to policy and practice. Interpretation: This framework aims to aid the translation of rigorous research methods into the standard development, monitoring, and evaluation cycles of commissioned health interventions, and to support researchers to evaluate real-life interventions. Registration is required before the tools can be downloaded, thus allowing us to commission an independent evaluation of these tools, planned for 2019. Funding: Big Lottery Fund (as part of the A Better Start programme), National Institute for Health Research (NIHR) Collaboration for Leadership in Applied Health Research and Care Yorkshire and Humber.